Dysconnectivity of the Agency Network in Schizophrenia: A Functional Magnetic Resonance Imaging Study - Koreki, Akihiro; Maeda, Takaki; Okimura, Tsukasa; Terasawa, Yuri; Kikuchi, Toshiaki; Umeda, Satoshi; Nishikata, Shiro; Yagihashi, Tatsuhiko; Kasahara, Mari; Nagai, Chiyoko; Moriyama, Yasushi; Den, Ryosuke; et al. (Frontiers in Psychiatry, 2019)
Background: Self-disturbances in schizophrenia have begun to be explained by an abnormality in the sense of agency (SoA). The cerebral structures of SoA in healthy people are considered to mainly include the insula and inferior parietal lobule. In contrast, the functional lesion of aberrant SoA in schizophrenia is not yet fully understood. Considering the recent explanation of establishing SoA from the standpoint of associative learning, the “agency network” may include not only the insula and inferior parietal lobule but also the striatum. We hypothesized that aberrant SoA in schizophrenia is based on a deficit in the “agency network”. Methods: Functional magnetic resonance imaging data were acquired while patients with schizophrenia (n = 15) and matched controls (n = 15) performed our adaptation method of agency attribution task on a trial-by-trial basis to assess participants’ explicit experience of the temporal causal relationship between an action and an external event with temporal biases. Analysis of functional connectivity was done using the right supramarginal gyrus and the right middle frontal gyrus as seed regions. Results: In healthy controls, analyses revealed increased activation of the right inferior parietal lobule (mainly the supramarginal gyrus), right insula, and right middle frontal gyrus as an activation of the agency condition. We defined activated Brodmann areas shown in the agency condition of healthy controls as the seed region for connectivity analysis. The connectivity analysis revealed lower connectivity between the head of the left caudate nucleus and right supramarginal gyrus was observed in the patients compared to healthy controls. Conclusions: This dysconnectivity of the agency network in schizophrenia may lead to self-disturbance through deficits in associative learning of SoA. These findings may explain why pathological function of the striatum in schizophrenia leads to self-disturbance.